Filsafat Ilmu Design Based Learning (DBL) pada Pendidikan Vokasi: Ontologi, Epistemologi, dan Aksiologi - Sussi Widiastuti; Siti Masitoh; Mochamad Nursalim (Pusat Studi Bahasa dan Publikasi Ilmiah, 2022)
The world has entered the era of knowledge-based society and economy which is open (digital) and relies on free competition. The new era brought changes in the skills required by the job market. Vocational education and training at the secondary education needs to equip graduates with life and career skills: productivity and accountability in managing projects and producing products. Based on data from Badan Pusat Statistik (BPS) 2021, the ratio of the number of entrepreneurs in Indonesia is still 3.47 percent or only around 9 million people of the total population. The percentage of trading business owners who are graduates of Vocational High Schools (SMK) is 5.5%. Through the SMK revitalization program in 2020 it is hoped that conditions will be created in 80% of SMK graduates work in their fields, 12% are entrepreneurs, and 8% continue their studies. SMK gradute can be identified by the competency of each expertise program, so that the existence of products or applied results for society is absolutely there. A learning concept that can facilitate SMK students in producing products is a design-based learning/DBL. DBL as a science is an activity of knowledge and explanation that has direction and purpose. This activity is carried out with certain procedures, using methods, steps and means of support. Philosophy of science invites people to reflect on their knowledge activities through three foundations of discussion, namely: ontology, epistemology, and axiology. This literature study aims to examine the DBL framework from three aspects above.